A New Index to Describe the Relationship between Solar Extreme Ultraviolet Variation and Solar Activity - Chen, Zhou; Zhou, Kecheng; Wang, Jing-Song; Song, Qiao; Ouyang, Zhihai; Li, Haimeng; Zhou, Meng; Deng, Xiaohua (The Astrophysical journal, 2023)
In this paper, a new solar activity index based on a novel disturbance extraction method, the spectral whitening method (SWM), is introduced to process the solar EUV data on the Atmospheric Imaging Assembly (AIA) on board the Solar Dynamics Observatory. Our research suggests that the spatial information derived by SWM can well reflect the location of disturbance extraction, which is consistent with the location of the solar active region. It indicates that the disturbance extraction is effective. From AIA 094 Å to AIA 335 Å, SWM results are strongly correlated with solar radio flux F107 and the sunspot number (SSN), especially at AIA 211 Å, where the correlation coefficient reaches the maximum, while at AIA 1600 Å and AIA 1700 Å there are no detectable correlations. The proposed new solar activity index, J P AIA , has the following characteristics: (1) the new index can reflect the main variations of F107 and SSN, indicating that the index is valid; (2) the new index has higher temporal resolution, which is more conducive to the more detailed study of solar activities on short timescales; (3) the new index reveals that the solar atmosphere still has significant variability during solar minimum characterized by low F107 and SSN; (4) the new index can be used in conjunction with the new magnetospheric and ionospheric indices, which are also derived by SWM to deepen the understanding of the causal chain of space weather and promote the improvement of forecasting capabilities.